2023
DOI: 10.1027/1866-5888/a000304
|View full text |Cite
|
Sign up to set email alerts
|

Improving Employee Mental Health Through an Internet-Based Job Crafting Intervention

Abstract: This article examined the impact of an online job crafting intervention (JCI) on employees’ ill-being and well-being at work, as measured by irritation and job satisfaction. To address this question, this study used an experimental design with randomized intervention and control groups. Recruited subjects ( N = 208) participated in a four-week web-based JCI, which consisted of one training session and three reflection sessions. The study outcomes were measured at three time points: before the intervention (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…However, more recently, Verelst et al (2021) tested an electronic job crafting intervention and concluded that it represents an effective alternative to traditional interventions based on the observation of significant increases in job crafting following the tested intervention. Elsewhere, testing an online intervention as part of the EngAGE‐Coach program, Uglanova and Dettmers (2022) recorded a significant reduction in irritation among participants of the intervention group.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, Verelst et al (2021) tested an electronic job crafting intervention and concluded that it represents an effective alternative to traditional interventions based on the observation of significant increases in job crafting following the tested intervention. Elsewhere, testing an online intervention as part of the EngAGE‐Coach program, Uglanova and Dettmers (2022) recorded a significant reduction in irritation among participants of the intervention group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other studies refer to the protective function of job crafting for employees’ mental health, e.g. by reducing exhaustion [ 25 , 29 , 30 ]. If the categories are integrated in the JDR model, the blurred work and life domains impact employees as a job demand when WFH, while boundary management and energy resources management can function as strategies to reduce exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In general, job crafting behavior has been found to be a protective factor for employees’ mental health [ 25 ] due to the reduction of psychological distress [ 22 , 26 ], burnout [ 27 , 28 ], and exhaustion [ 29 , 30 ]. For an overview of the positive outcomes of job crafting on employees’ health and mental health such as effects on well-being, resilience, vitality, reduced fatigue, reduced distress [ 13 , 14 ].…”
Section: Job Demands-resources Model (Jd-r Model) and Job Craftingmentioning
confidence: 99%
“…More specifically, to promote job crafting, organizations could offer both online and offline intervention approaches as both forms were shown to be effective in increasing job crafting (Uglanova & Dettmers, 2022; Van Wingerden et al, 2017; Verelst et al, 2021). Furthermore, given that crafting is related to leadership, supervisors should lead by example, grant employees the autonomy to craft their jobs, and transfer effective home crafting behaviours to the work domain (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, employees may proactively attempt to change the characteristics of their jobs in order to balance their demands and resources with their abilities and needs; that is, they may engage in job crafting to achieve optimal functioning (Tims et al, 2012;Wrzesniewski & Dutton, 2001). Recent meta-analyses (Boehnlein & Baum, 2020;Lichtenthaler & Fischbach, 2018;Rudolph et al, 2017) and intervention research (Oprea et al, 2019;Uglanova & Dettmers, 2022) confirmed that job crafting is indeed beneficial for employee well-being, engagement, and performance.…”
Section: Introductionmentioning
confidence: 99%